Tanggapan Siswa Terhadap Nilai Pendidikan Yang Terkandung Dalam Humor Pada Wacana Rubrik Hiburan Majalah Sekolah - Astuti, Anita, Prof. Dr. Markamah, M.Hum (2016)
Abstracts This study has two goals. (1) Examines the value of education contained in humour in the discourse rubric of the magazine school based on the interpretation of the researchers. (2) Explained the responses students against the value of education contained in humour in the discourse rubric of the magazine school. Methods used is thedescriptive kualitatif. Object scrutinized are the values education contained in humour in the discourse rubric of the magazine school based on the interpretation of the researchers and students. Collecting data technique used in this study is a listen and technique catat. The techniques data analysis in this research using the match with match referensial. The results of research shows that the value of education contained in humour in the discourse rubric of the magazine school based on the interpretation of students covering the value of the responsibility, the value of love, the value of tolerance, the value of the honesty, the value of the award, the value of happiness, the value of unity, the value of the humility, and the value of manners, while the value of education contained in humour in the discourse rubric of the magazine school based on the interpretation of the researchers covering the value of the responsibility, the value of love, the value of tolerance, the value of the honesty, the value of the award, the value of happiness, the value of unity, and the value of humility. There are the similarities and differences between the two interpretation of it. The difference both located in the value of happiness and the value of manners. However, most of the data shows the existence of the equation of both the interpretation of it. This proves that the ability to students in understand the discourse humor and respond to the values of education contained in the discourse humor is good enough. Key words: the responses students, the value of education, humor, the magazine school.